PENGARUH BEBAN KERJA DAN KOMPENSASI TERHADAP KINERJA PEGAWAI SEKRETARIAT PEMERINTAH DAERAH KABUPATEN TABANAN - Paramitadewi, Kadek Ferrania (E-Jurnal Manajemen, 2017)
This study aims to determine the effect of workload and compensation to employee performance Local Government Secretariat Tabanan regency. The study was conducted at the Regional Administration of the Office of Tabanan Regency Tabanan Regent. Local Government Tabanan regency is located at Jl. Heroes, delod Peken, Tabanan. The samples were 76 employees, using probability sampling methods. The data analysis technique applied is multiple linear regression. The results of the analysis said that the workload of a significant negative effect on employee performance. This influence means that the lower the workload of employees, the higher the employee's performance against the Local Government Secretariat Tabanan regency. Results also showed that the positive and significant compensation TerhadapKinerja Employees. This means that the level of compensation affects employee performance Local Government Secretariat Tabanan regency. Party leaders should pay attention to the provision of workload to employees in accordance with the abilities and skills of each employee, so that employees can feel more comfortable in doing his job.
Keywords: Beban Kerja; Kompensasi; Kinerja Pegawai